Education On Understanding Of Information And Electronic Transaction Laws In The Context Of Social Media - Tyna Yunita; Murti Wijayanti; Heni Rohaeni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The mother acts as an educator in the family. In addition, a mother is also an individual who has many activities. Mothers use social media as a source of information, socialization, and knowledge sharing in their daily activities. In addition, women have limited knowledge but are vulnerable to risk from social media users or certain family members. Participants' knowledge and understanding of social media were still minimal. This community service activity aims to teach mothers participating in the Jami At-Taqwa Mosque recitation of Information and Electronic Transactions and learning to use social media wisely. Initial observation and discussion were the initial resistance to this activity. The second stage was the material presentation activities, followed by the third stage, namely discussions with training participants. Participants' understanding increased by 73% of those who did not know at first. In addition, the discovery of social media selection based on the first reason is easy; the second is usefulness. Interestingly, the security aspect is not of particular concern. This activity increased insight and intellectual capital used in the family and the community.